2015
DOI: 10.3390/s150819667
|View full text |Cite|
|
Sign up to set email alerts
|

Towards the Development of a Low Cost Airborne Sensing System to Monitor Dust Particles after Blasting at Open-Pit Mine Sites

Abstract: Blasting is an integral part of large-scale open cut mining that often occurs in close proximity to population centers and often results in the emission of particulate material and gases potentially hazardous to health. Current air quality monitoring methods rely on limited numbers of fixed sampling locations to validate a complex fluid environment and collect sufficient data to confirm model effectiveness. This paper describes the development of a methodology to address the need of a more precise approach tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 19 publications
1
77
1
2
Order By: Relevance
“…Multicopters offer flexible maneuverability at low flight speed and the possibility of hovering (i.e., no horizontal movement). Their applications include meteorological and air quality measurements, e.g., particulate matter (Alvarado et al, 2015) or air samples for analyses of chemical composition (Chang et al, 2016), but on a smaller scale of several hundreds of meters. In addition, Neumann and Bartholomai (2015) and Palomaki et al (2017) showed that the onboard flight control sensors can be used to derive wind estimates from a multicopter's attitude control data.…”
Section: Introductionmentioning
confidence: 99%
“…Multicopters offer flexible maneuverability at low flight speed and the possibility of hovering (i.e., no horizontal movement). Their applications include meteorological and air quality measurements, e.g., particulate matter (Alvarado et al, 2015) or air samples for analyses of chemical composition (Chang et al, 2016), but on a smaller scale of several hundreds of meters. In addition, Neumann and Bartholomai (2015) and Palomaki et al (2017) showed that the onboard flight control sensors can be used to derive wind estimates from a multicopter's attitude control data.…”
Section: Introductionmentioning
confidence: 99%
“…Dust raised by blasting is one such example [10,11]. In passing it is worth a comment that the main purpose of blasting is comminution (reducing overburden and coal to a convenient size for handling by trucks and excavators).…”
Section: The Use and Limitations Of Emission Factorsmentioning
confidence: 99%
“…Industry has mostly been slow to modernise its techniques [11] such as exploiting nitrogen dioxide fume patterns to quantify the dispersal of respiratory dust. Even more useful than this is the use of drones for this purpose, developed by university researchers [10] and younger more entrepreneurial companies [12].…”
Section: The Use and Limitations Of Emission Factorsmentioning
confidence: 99%
“…These requirements may impact other dimensions of the design space such as coverage and resources [6]. Current security mechanisms in ad-hoc sensor networks do not guarantee reliable and robust network functionality.…”
Section: E Security Architecture and Requirements Of Wireless Sensormentioning
confidence: 99%